Remaining life definition of crane metal construction on value of coercive forces - Grigorov, O. V.; Gubskiy, S. O.; Strizhak, V. V.; Okun, A. O. (University of Petrosani, 2012)
In this work, the condition definition of bridge crane metal construction and prognostication of its remaining life on the basis of nondestructive control method by using coercive forces is presented. Basic approaches and performance stages of the magnetic control for the purpose of metal condition definition and remaining life of its work are considered
Keywords: bridge crane; nondestructive control method